Experimental study of transmission of ultrasonic wave in optical fibers - MUC, Sylwia (Archives of Acoustics, 2008)
Optical waveguides are commonly used to transmit electromagnetic radiation. The possibility of acoustic wave propagation in optical waveguides creates new prospects for simultaneous transmission of laser beam and ultrasonic wave. The measurements of the transmission of ultrasound in optical waveguides were performed for three representative types of optical fiber: a multimode step refractive index, a single-mode step refractive index and a multimode graded refractive index. Amplitude characteristics of signal propagated in optical waveguides of the three types of optical waveguides are given in this paper. The frequencies, for which amplitude maxima were obtained, overlapped resonant frequencies of a thick vibrating piezoelectric disk, which was the source of the ultrasonic waves.